2021
DOI: 10.1186/s13014-021-01776-8
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy of oligometastatic prostate cancer: a systematic review

Abstract: Background Due to improved imaging sensitivity, the term “oligometastatic” prostate cancer disease is diagnosed more often, leading to an increasing interest in metastasis-directed therapy (MDT). There are two types of radiation based MDT applied when treating oligometastatic disease: (1) stereotactic body radiation therapy (SBRT) generally used for bone metastases; or (2) SBRT for isolated nodal oligometastases combined with prophylactic elective nodal radiotherapy. This review aims to summari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 88 publications
5
32
0
Order By: Relevance
“…In addition to conventional imaging methods using CT and bone scintigraphy, many reports have used positron emission tomography-CT (PET-CT) using 18 F-fluorodeoxyglucose and 11 C-choline, as well as whole-body MRI (WB-MRI) for diagnosis. Shen et al conducted a meta-analysis of the diagnostic performance of bone metastases and reported that choline PET-CT, MRI, and bone scintigraphy had sensitivities of 87%, 95%, and 79%, respectively, and specificities of 97%, 96%, and 82%, respectively [86].…”
Section: Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to conventional imaging methods using CT and bone scintigraphy, many reports have used positron emission tomography-CT (PET-CT) using 18 F-fluorodeoxyglucose and 11 C-choline, as well as whole-body MRI (WB-MRI) for diagnosis. Shen et al conducted a meta-analysis of the diagnostic performance of bone metastases and reported that choline PET-CT, MRI, and bone scintigraphy had sensitivities of 87%, 95%, and 79%, respectively, and specificities of 97%, 96%, and 82%, respectively [86].…”
Section: Diagnosismentioning
confidence: 99%
“…The goals may be to control the cancer, slow down further metastasis, and avoid or delay systemic therapyrelated toxicity. A systematic review has given an overview of the current evidence for MDT in oligometastatic PC [11]. Local control rates at two years ranged between 76-100%.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…16 The interest towards PSMA-targeted imaging has increased during the last years, as, thus far, it was proven to have the highest metastases detection rates over the other available imaging methods. 8 In particular, studies showed 68 Ga-PSMA PET/CT consistently outperforming choline PET/CT at low PSA values, 20 with reported detection rates of 15-58%, 25-73%, 69-100% for PSA ranges of 0.2-0.5 ng/mL, 0.5-1 ng/mL and 1-2 ng/mL, respectively. 8 Moreover, a high level of interobserver agreement was demonstrated for 68 Ga-PSMA PET/ CT, both for nodal and bony lesions.…”
Section: Imaging In Ompcmentioning
confidence: 99%
“…8 In particular, studies showed 68 Ga-PSMA PET/CT consistently outperforming choline PET/CT at low PSA values, 20 with reported detection rates of 15-58%, 25-73%, 69-100% for PSA ranges of 0.2-0.5 ng/mL, 0.5-1 ng/mL and 1-2 ng/mL, respectively. 8 Moreover, a high level of interobserver agreement was demonstrated for 68 Ga-PSMA PET/ CT, both for nodal and bony lesions. 21,22 Admittedly, PSMA-based techniques may fail to detect clinical progression when PSMA is either absent or scarcely expressed.…”
Section: Imaging In Ompcmentioning
confidence: 99%